MORPHOLOGICAL AND ANATOMICAL INVESTIGATIONS INTO THE MECHANISM OF LEAF PAIR UNROLLING IN URARIA PICTA (JACQ.) DESV. EX DC. (PAPILIONACEAE), A MEDICINAL PLANT IN NIGERIA - Oyesiku, O. O.; Okusanya, O. T.; Olowokudejo, J. D. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Uraria picta leaf-pair unrolling inside out is a remarkable feat. A leaf-pair was investigated to understand the mechanism of spontaneous reverse inside out act of the plant. The upper (adaxial) and lower (abaxial) surfaces of the leaf-pair were examined using scanning and light microscopy. The scan showed diversity of hairs varying in shape from straight, pointed, curve, and club to hook. There were deposits of wax on both sides of the leaf-pair. The light microscope showed hairs are restricted to the midrib on the adaxial surface of the leaflets missing. Hooked hairs dominated the entire abaxial surface of the leaflets. The transverse section of the midrib section showed abundance of structural and mechanical tissues, collenchyma and sclerenchyma tissues. Both morphological and anatomical attributes were used to explain the mechanism and how the plant got its Yoruba vernacular name ‘Alupayida’ as well as its purported use in changing the sex of the unborn child and in breaking up love affairs.